The Relationship Between Self-Esteem and Bullying Among Middle School Students - Salsabila, Sartika; Firman, Firman (The Future of Education Journal, 2025)
This research is motivated by the high number of students engaging in bullying behavior towards their peers. One factor that influences bullying behavior is self-esteem. The aim of this study is to describe: 1) self-esteem among students, 2) bullying behavior among students, and 3) the relationship between self-esteem and bullying behavior among students. This research uses a quantitative method with a correlational research design. The population in this study consisted of 127 students from SMPN 2 2X11 Enam Lingkung, using the Total Sampling technique, resulting in a total sample of 127 students. Data collection was conducted using self-esteem questionnaires and bullying behavior questionnaires. The data were processed using descriptive analysis techniques and Pearson product-moment correlation analysis with the assistance of SPSS version 20.0 for Windows. The results of this study show that: 1) the self-esteem of students at SMPN 2 2X11 Enam Lingkung is generally categorized as high, with 54 students (45.52%) in this category; 2) bullying behavior among students at SMPN 2 2X11 Enam Lingkung is generally categorized as moderate, with 76 students (59.84%) in this category; 3) there is a significant negative relationship between self-esteem and bullying behavior among students at SMPN 2 2X11 Enam Lingkung, with a correlation coefficient of -0.245 and a significance level of 0.006. Based on the results of this study, guidance and counseling services that can be provided to improve self-esteem and reduce bullying behavior among students include information services, individual counseling services, and group counseling services.